Microbial driver of 2006–2023 CH 4 growth indicated by trends in atmospheric δD–CH 4 and δ 13 C–CH 4 - Ben Riddell-Young; Sylvia Englund Michel; Xin Lan; Pieter Tans; Thomas Röckmann; Bibhasvata Dasgupta; Youmi Oh; Lori M. P. Bruhwiler; Ryo Fujita; Taku Umezawa; Shinji Morimoto; John B. Miller (Proceedings of the National Academy of Sciences, 2025)
Methane (CH 4 ) is the second most important greenhouse gas and has been rising following a brief period of stabilization from 1999 to 2006. Determining the cause of this rise is critical for reducing emissions and predicting future climate sensitivity. The carbon and hydrogen stable isotopic composition of atmospheric CH 4 is controlled by variability in isotopically distinguishable emission categories and fractionating sink processes. While most studies using atmospheric δ 13 C–CH 4 data suggest a dominantly microbial source for recent CH 4 growth, this understanding is not uniform, and uncertainties remain [S. Schwietzke et al. , Nature 538 , 88–91 (2016), S. Basu et al. , Atmos. Chem. Phys. 22 , 15351–15377 (2022), J. Thanwerdas, M. Saunois, A. Berchet, I. Pison, P. Bousquet, Atmos. Chem. Phys. 24 , 2129–2167 (2024)]. Here, we present a harmonized global measurement record of atmospheric δD–CH 4 and estimate emissions from 1999 to 2022 with global isotope mass balance calculations using both carbon and hydrogen isotopic ratios. We conduct thorough uncertainty analyses to separate absolute magnitude and emission trend uncertainties and find with high confidence that trends in δ 13 C–CH 4 and δD–CH 4 observations are both consistent with an entirely microbial emission driver of the post-2006 CH 4 rise, while fossil fuel emissions have remained relatively stable.